Land use and land cover change detection and spatial distribution on the Tibetan Plateau - Shuang Hao (Nature Portfolio, 2021)
Abstract Regarded as the third pole of the Earth, the Tibetan Plateau (TP) is a region with complex terrain. Vegetation is widely distributed in the southeastern part of the plateau. However, the land use and land cover changes (LULCC) on the TP have not been sufficiently studied. In this study, we propose a method of studying the dynamic changes in the land cover on the TP. Landsat OLI images (2013 and 2015) were selected to extract the LULCC information of Nyingchi County, the DEM was used to extract objects’ land curved surface area and analyze their three-dimensional dynamic change information, which realized a four-dimensional monitoring of the forestry information on time and spatial level. The results showed that the forest area in 2015 decreased by 7.25%, of which the coniferous forest areas decreased by 25.14%, broad-leaved forest areas increased by 12.65%, and shrubbery areas increased by 14.62%. Compared with traditional LULCC detection methods, the change detection is no longer focused on the two-dimensional space, which helps determine the three-dimensional land use and land cover changes and their distribution. Thus, dynamic spatial changes can be observed. This study provides scientific support for the vegetation restoration and natural resource management on the TP.